Contributing factors toward the usage of 'Mobile Apps Learning' application among Malaysian museum visitors / Nur Nabihah Mohamad Nizar - Mohamad Nizar, Nur Nabihah (2015)
Museum is one of educational centre for people to gain knowledge. Varieties communication modes have been used to deliver information toward museum visitors. The advent of technology has brought to the usage of mobile technology in museum, thus ensure visitor’s meaningful experiences. Further, the integration of mobile technology in museum has facilitated visitor’s understanding on information about artifacts in the museum. In addressing this issue, the present study focused on designing a 'Mobile Apps. Learning' application as an approach to deliver an information to museum’s visitor. The study also aims to determine the usability, and factors that might influence museum visitors' usage of 'Mobile Apps. Learning' application, that was self-developed for this study. Systematic instructional materials procedures and phases were implemented in designing the “Mobile Apps. Learning’ application. Data of the study was collected through fifty responses from a survey questionnaire. Visual communication elements was the best guidelines in designing 'Mobile Apps. Learning' application. It indicates that the application was usable in delivering an information towards museum visitors'. Besides, satisfaction is the best predictor in the direction of the usage of 'Mobile Apps. Learning' application. As a conclusion, the present study would like to suggests that the development and implementation of the 'Mobile Apps. Learning' application is beneficial to museum visitor in gaining their knowledge, thus need to be continually integrated into all museum.